Validation of the Arts Observational Scale (ArtsObS) for the evaluation of performing arts activities in health care settings. Issue 2 (3rd May 2016) - Fancourt, Daisy; Poon, Michelle
Abstract : Background : As the number of arts-in-health programmes globally continues to increase, there is an growing need for a systematic approach to evaluation both to provide evidence of the efficacy of projects and support continuous quality improvement. The Arts Observational Scale (ArtsObS) is proposed as a mixed-methods tool to evaluate performing arts activities in health care settings. Methods : The tool was developed over two years involving a consultation process with 1, 500 patients, relatives and staff, and validated over a six-month period with 805 patients. Construct validity was assessed through extensive literature reviews, and score distributions, inter-rater reliability and concurrent validity were assessed using Pearson's/Spearman's coefficient. Results : Organising constructs were grounded in both empirical and theoretical research. Data collected with the tool were well distributed. Inter-rater reliability was very strong ( r  = .721, p  < .001) and concurrent validity was strong ( r  = .641, p  < .001). Conclusions : ArtsObS is a reliable way of evaluating the impact of arts programmes in health care settings and is recommended to practitioners, project managers and researchers.